THE EFFECTIVENESS OF PENJAS LEARNING DURING THE COVID-19 PANDEMIC IN JUNIOR HIGH SCHOOLS IN STABAT DISTRICT - Barus, Aldiansyah Putra; Damanik, Saipul Ambri (Journal of Physical Education, Health and Sports Recreation, 2023)
This research was motivated by some time ago due to the COVID-19 outbreak that hit the world at the end of 2019 until now at the beginning of 2022. This research aims to determine the effectiveness of online learning in physical education subjects in junior high schools throughout the Stabat District. This research is a descriptive research with a survey method. The data collection technique uses a questionnaire with a total sample of 90 students. The data analysis technique used to present the data uses descriptive statistics with percentages. The results of this study indicate the level of effectiveness of physical education learning in junior high schools in the Stabat district for the 2021/2022 school year during the Covid-19 pandemic was at a "low" level. With the "Very High" category as many as 14% of all respondents, the "High" category as many as 17% of respondents, the "Medium" category as many as 21% of respondents, the "Low" category as many as 47% of respondents, and the "Very Low" category as much as 1% of the total number of respondents. These results indicate the level of effectiveness of physical education learning in junior high schools in the Stabat district is carried out with "less". It is hoped that teachers can improve the quality of implementing physical education learning so that they can improve students' abilities in junior high schools throughout the Stabat District.